SPIRITUALITY AND RESILIENCE IN MEDICAL STUDENTS; A CROSS SECTIONAL STUDY - Hilmy, Farhan; Wiyono, Nanang; Hastami, Yunia; Munawaroh, Siti (International Journal of Islamic and Complementary Medicine, 2024)
Resilience plays a very important role for medical students. The formation of resilience in overcoming problems is closely related to spirituality. Spirituality helps individuals see problems as part of the learning and growth process. The aim of this research is to identify whether there is a positive relationship between the level of spirituality and the level of resilience. This research is an analytical observational research with a cross sectional approach. Sampling was carried out using a random sampling technique with a total research sample of 100 medical students. Measurement of the level of spirituality was carried out using the Daily Spiritual Experience Scale (DSES) questionnaire, while measurement of the level of resilience was carried out with the Connor-Davidson Resilience Scale (CD-RISC 25) questionnaire. Bivariate analysis of the two variables used the Spearman correlation test. The result of the bivariate analysis test using Spearman obtained a significance value of p<0,05 which shows that the relationship between the independent variable and the dependent variable is significant. The level of spirituality and the level of resilience is positively correlated in medical students.